PENGARUH CAHAYA,TEMPERATUR DAN SHIFT KERJA TERHADAP KINERJA OPERATOR - Simanjuntak, Risma Adelina; Christy, Nikolaus (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2004)
The result from operator worked was influenced by various existing system. This condition is not quit from the condition of physical environment work around operator and indirectly influence result of human being performance / the operator. This condition will be happened at one particular work which is needing high concentration and yield optimal performance time. Therefore this research purposes and objectives is to analyse the influence between light, work shift and temperature either through individual and or simultan. This research is done in soundproof space so the operator can yielding the optimal output. Pursuant to result of analysis with factorial experiment, ANOVA, 3 factor, test T, Test F which have known that having influence to operator performance is light, temperature, and work shift either through individual and or simultan with mistake storey level : 5 % shown with f value (count) > F( tables). Result of this research depict about yielded ability storey; level by human being in working which is resulted by the existence of third factor which is treatment was tested.the three condition which has been tested give conclusion that yielding optimal in working is light 170 Lux.,Temperatur 30-32 0 C, and shift work morning.